A Smart Driver Monitoring System Using Android Application and Embedded System - Alsibai, Mohammad Hayyan; Hoo, Min Sing (2015)
This paper proposes a new integrated driver monitoring system. The system is combining a smartphone App and an embedded controller to build a smart controlling and monitoring system. Nowadays smartphones are equipped with many useful built-in sensors. Moreover, embedded controllers are able to be connected to various analogue and digital sensors. In the proposed system a Bluetooth module is used to exchange data between the smartphone, the embedded controller and the built-in and external sensors. The system is a comprehensive monitoring device for employee driver performance. Moreover, it guarantees full privacy protection. The system was tested in real modes.